Register
Register

Answer :

Given tan-1 {2 sin (2 cos-1 √3/2)}


= tan-1 {2 sin (2 cos-1 cos π/6)}


= tan-1 {2 sin (2 × π/6)}


= tan-1 {2 sin (π/3)}


= tan-1 {2 × √3/2}


= tan-1 {√3}


= π/3


tan-1 {2 sin (2 cos-1 √3/2)} = π/3


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

State True or FalMathematics - Exemplar

State True or FalMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Find the principaRD Sharma - Volume 1

State True or FalMathematics - Exemplar

State True or FalMathematics - Exemplar